2006
DOI: 10.1080/15421400600654108
|View full text |Cite
|
Sign up to set email alerts
|

Fredericksz Transition Threshold in Nematic Liquid Crystals Filled with Ferroelectric Nano-Particles

Abstract: A key liquid crystalline property for electro-optic applications is the Frederiks threshold electric field. There has been recent experimental interest in liquid crystal-based colloidal suspensions in which the colloidal nanoparticles both possess a permanent electric polarization and provide strong director anchoring on the particle surface. Such suspensions are sometimes known as Filled Liquid Crystals. Our calculations suggest, in qualitative agreement with experiment, that filling the nematic liquid crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 6 publications
0
35
0
Order By: Relevance
“…In previous theoretical research, Reshetnyak et al have developed a theoretical approach based on electrostatics [12,13,15]. In this theory, the key issue is how an ensemble of nanoparticles with aligned dipole moments can polarize the liquid-crystal molecules, hence increasing the intermolecular interaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous theoretical research, Reshetnyak et al have developed a theoretical approach based on electrostatics [12,13,15]. In this theory, the key issue is how an ensemble of nanoparticles with aligned dipole moments can polarize the liquid-crystal molecules, hence increasing the intermolecular interaction.…”
Section: Introductionmentioning
confidence: 99%
“…One particularly interesting case occurs if the particles are ferroelectric. Experiments have shown that low concentrations of ferroelectric Sn 2 P 2 S 6 or BaTiO 3 nanoparticles increase the orientational order parameter, increase the isotropic-nematic transition temperature, and decrease the switching voltage for the Frederiks transition [7][8][9][10][11][12][13][14]. Thus, they provide a new opportunity to enhance the properties of liquid crystals for technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The fields χ k ( y) and R k ( y), k = 1,2,3 that appear in Eqs. (16) and (19) are the solutions of the two sets of cell problems.…”
Section: Homogenizationmentioning
confidence: 99%
“…Because the orientation of the dopants is correlated with the director, the orienting effect of the applied field on the dopants is felt by the nematic. Current theories on liquid crystals doped with ferromagnetic [16][17][18][19][20] or ferroelectric [21,22] particles assume a mean field interaction between the particles and the director field.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of such materials, in most cases, significantly differ from those of the host materials. In the past few years there has been a significant increase in the number of published articles dealing with use of metallic, semiconducting, ferromagnetic or ferroelectric nanoparticles, fullerenes and carbon nanotubes in mixture with liquid crystals [1][2][3][4]. Depending on experimental parameters such as nanoparticle functionalization and concentration, size and core material, cell surface treatment, as well as applied electric or magnetic field diverse effects arise in different nematic liquid crystal hosts [4,5].…”
Section: Introductionmentioning
confidence: 99%